Uji Kinerja Mesin Pengiris Singkong Tipe Vertikal - Annisa Nur Ichniarsyah; Eka Widiono; Titis Pury Purboningtyas (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2021)
Several efforts to improve the efficiency and effectiveness of slicing cassava machine had been conducted. One of them including the development of a prototype cassava slicing machine. This machine has types and classification based on slicing capacity. The purpose of this study was to conduct a machine performance test (verification test, performance test, and ergonomics test), to compare its performance with SNI 0838-1:2014, to analyze the constraints of a vertical cassava slicing machine. A quantitative research approach and descriptive explanatory method were used by observing, measuring, and calculating, the testing of cassava slicing machine. Verification test was to check the suitability of the type and type of engine, motor, transmission type, slicing unit, engine frame, and other supporting components in accordance with the specifications. The performance results of the slicing machine displayed that its capacity was 18.51 kg/hour and performance efficiency of 74.05%. The slicing test obtained an average thickness was 0.73 mm, uniformity level of 64.2%, and damage rate around 9.67%. Ergonomics tests showed that the machine was quite in accordance with the comfort of the operator. There were some obstacles that need evaluations such as the difficulty in adjusting slicing blade, transmission, and technical specifications of the cassava slicing machine. Therefore, the cassava slicing machine needed improvement so that it conforms to the requirements that refer to SNI 0838-1:2014.  Keywords: cassava, performance test, slicing, slicing machine, testing